Hepatitis B virus reactivation in hepatitis B virus surface antigen negative patients receiving immunosuppression: A hidden threat - Zachou, Kalliopi (Baishideng Publishing Group Co., Limited, 2013)
AIM: To present the characteristics and the course of a series of anti-hepatitis B virus core antibody (HBc) antibody positive patients, who experienced hepatitis B virus (HBV) reactivation after immunosuppression. METHODS: We retrospectively evaluated in our tertiary centers the medical records of hepatitis B virus surface antigen (HBsAg) negative patients who suffered from HBV reactivation after chemotherapy or immunosuppression during a 3-year period (2009-2011). Accordingly, the clinical, laboratory and virological characteristics of 10 anti-HBc (+) anti-HBs (-)/HBsAg (-) and 4 anti-HBc (+)/antiHBs (+)/HBsAg (-) patients, who developed HBV reactivation after the initiation of chemotherapy or immunosuppressive treatment were analyzed. Quantitative determination of HBV DNA during reactivation was performed in all cases by a quantitative real time polymerase chain reaction kit (COBAS Taqman HBV Test; cut-off of detection: 6 IU/mL). RESULTS: Twelve out of 14 patients were males; median age 74.5 years. In 71.4% of them the primary diagnosis was hematologic malignancy; 78.6% had received rituximab (R) as part of the immunosuppressive regimen. The median time from last chemotherapy schedule till HBV reactivation for 10 out of 11 patients who received R was 3 (range 2-17) mo. Three patients (21.4%) deteriorated, manifesting ascites and hepatic encephalopathy and 2 (14.3%) of them died due to liver failure. CONCLUSION: HBsAg-negative anti-HBc antibody positive patients can develop HBV reactivation even 2 years after stopping immunosuppression, whereas prompt antiviral treatment on diagnosis of reactivation can be lifesaving.